State-of-the-Art of CO2 Capture with Ionic Liquids - Ramdin, Mahinder; de Loos, Theo W; Vlugt, Thijs J.H (Industrial & engineering chemistry research, 2012)
Economical and environmental aspects are the main motivation for research on energy efficient processes and the search for environment friendly materials for CO2 capture. Currently, CO2 capture is dominated by amine-based (e.g., monoethanolamine) technologies, which are very energy intensive and less attractive from an environmental point of view due to emissions of the used volatile solvent components. Ionic liquids have been proposed as a promising alternative to the conventional volatile solvents, because of their low volatility and other interesting properties. This remarkable interest has led to a rapid growth of literature on this specific subject. The aim of the present review paper is to provide a detailed overview of the achievements and difficulties that has been encountered in finding a suitable ionic liquid for CO2 capture from flue-gas streams. A major part of this review includes an overview of the experimental data of CO2 solubility, selectivity, and diffusivity in different ionic liquids. The effect of anions, cations, and functional groups on the CO2 solubility, biodegradability, and toxicity of the ionic liquids are highlighted. Recent developments on task-specific ionic liquids and supported ionic liquid membranes are also discussed. Scarcely available results of molecular simulations, which is a valuable tool in designing and evaluating ionic liquids, are also reviewed. The trends highlighted here can be used by solvent designers to navigate through the massive amount of theoretically possible ILs.